Umbilical metastasis (Sister Joseph's nodule) as a first sign of a disseminated ovarian carcinoma: comparative immunohistochemical analysis of primary tumor and its metastases. Issue 2 (1st February 2005) - Brasanac, D.; Boricic, I.; Todorovic, V.; Basta-Jovanovic, G.
Abstract : The case of a 46-year-old female with umbilical metastasis as a first sign of an ovarian carcinoma is reported with the results of immunohistochemical analysis of primary tumor and lymph node and umbilical metastases. All specimens were positive for cytokeratin 7, CA 125, E-cadherin, alpha-, beta-, and gamma-catenin, as well as for MSH2. Staining with cytokeratin 20 and MLH1 was negative, and Ki-67 labeled from 5% (in the center of the lesions) to over 25% (at the periphery of the lesions) of the nuclei. Beta-catenin showed membranous positivity in the central parts and absence of staining at the periphery of ovarian tumor and umbilical metastasis, whereas lymph node metastasis presented with uniform reaction throughout. The results of immunohistochemical staining could point to the mechanisms employed by malignant tumors during invasion and growth of metastasis and suggest the possible role of the microenvironment in the expression of some adhesion molecules on tumor cells